The People's Republic of China- Japan- United States integration amid global rebalancing: A computable general equilibrium analysis - Masahiro Kawai; Fan Zhai (Asian Development Bank Institute (ADBI), 2009)
Using a global general equilibrium trade model, this paper assesses the long-term implications of global rebalancing for Asian economies and explores the benefits of the People's Republic of China-Japan-United States integration. The analysis suggests that consumption evaporation, a growth slowdown in the US, and the consequent current account correction would force the People's Republic of China, Japan, and other East Asian economies to undergo substantial structural adjustments. A combination of domestic reform aimed at boosting service sector productivity and external liberalization aimed at fostering broader economic integration will be critical for East Asian economies to facilitate their economic rebalancing and sustained growth. Our global computable general equilibrium analysis suggests that the People's Republic of China and Japan need to strengthen their economic ties with the United States while at the same time bringing other East Asia economies into this integration process.
Keywords: C68; F15; 330